Dissipative non-equilibrium Green function methodology to treat short range Coulomb interaction: current through a 1D nanostructure - Antonio Martinez Muniz (Journal of Physics: Condensed Matter, 2018)
A methodology describing Coulomb blockade in the non-equilibrium Green function formalism is presented. We carried out ballistic and dissipative simulations through a 1D quantum dot using an Einstein phonon model. Inelastic phonons with different energies have been considered. The methodology incorporates the short-range Coulomb interaction between two electrons through the use of a two-particle Green function. Unlike previous work, the quantum dot has spatial resolution i.e. it is not just parameterized by the energy level and coupling constants of the dot. Our method intends to describe the effect of electron localization while maintaining an open boundary or extended wave function. The formalism conserves the current through the nanostructure. A simple 1D model is used to explain the increase of mobility in semi-crystalline polymers as a function of the electron concentration. The mechanism suggested is based on the lifting of energy levels into the transmission window as a result of the local electron–electron repulsion inside a crystalline domain. The results are aligned with recent experimental findings. Finally, as a proof of concept, we present a simulation of a low temperature resonant structure showing the stability diagram in the Coulomb blockade regime.